Development of Thematic Learning Materials Based on Scientific Approach on Indahnya Alam Negeriku Subtema in 4th Grade of Public Elementary School 094151 Sipanganbolon - Magdalena Sirait; Khairil Ansari; Naeklan Simbolon (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The aims of the study is to find out  the development of thematic learning materials based on scientific approach. The data was conducted in the IV grade student of SD Negeri 094151 Sipanganbolon Academic Year 2018/2019, the sample taken from 30 students. The result shows that the feasibility assessment by material experts obtained an average score of 3.27 and 81.94% (Very good), the feasibility assessment by linguists obtained an average score of 3.56 and 89% (Very good), the feasibility assessment by design experts obtained an average score of 3.4 and 85% (Very good).